Summation to Equation

Algebra Level 4

Consider the polynomial representation h ( x ) h(x) of f ( x ) = n = x x 2 n f(x) = \sum\limits_{n=x}^{x^2} n for all positive integers x x .

If h ( x ) h(x) has complex roots a 1 , a 2 , a 3 , a 4 a_1, a_2, a_3, a_4 , then evaluate the sum of the coefficients of the monic quartic polynomial g ( x ) g(x) possessing roots a 1 2 , a 2 2 , a 3 2 , a 4 2 a_1^2, a_2^2, a_3^2, a_4^2 .

1 -1 0 None of These 1/2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Alex Delhumeau
Mar 9, 2016

Consider some values of f ( x ) = n = x x 2 n f(x)=\sum\limits_{n=x}^{x^2}n .

f ( 1 ) = 1 f(1)=1 ; f ( 2 ) = 2 + 3 + 4 = 9 f(2)=2+3+4=9 ; f ( 3 ) = 3 + 4 + 5 + 6 + 7 + 8 + 9 = 42 f(3)=3+4+5+6+7+8+9=42 , etc.

Clearly, f ( x ) f(x) is the sum of the first x 2 x^2 positive integers minus the sum of the first x 1 x-1 positive integers. This is equivalent to ( x 2 ( x 2 + 1 ) 2 ( x 1 ) x 2 ) (\frac{x^2(x^2+1)}{2}-\frac{(x-1)x}{2}) , which simplifies to x 4 + x 2 \frac{x^4+x}{2} .

By inspection, two roots of this expression are 1 -1 & 0 0 . Dividing these out and applying quadratic formula to the resultant polynomial, we find the other two roots as 1 2 ± i 3 2 \frac{1}{2}\pm i\frac{\sqrt{3}}{2} .

Squaring all of these, we get 1 2 ± i 3 2 , 0 , -\frac{1}{2}\pm i\frac{\sqrt{3}}{2},0, & 1 1 .

Thus we find that g ( x ) = a x ( x 1 ) ( x + 1 2 i 3 2 ) ( x + 1 2 + i 3 2 ) = a x 4 a x 2 g(x)=ax(x-1)(x+\frac{1}{2}-\frac{i\sqrt{3}}{2})(x+\frac{1}{2}+\frac{i\sqrt{3}}{2})=\frac{ax^4-ax}{2} .

The sum of the coefficients, then, no matter what the leading coefficient a a may be, = 0 =\boxed{0} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...